Why we must fight biopiracy - Khor, Martin (Himalayan Journal of Sciences, 2006)
Martin Khor argues that a major effort is needed to prevent intellectual property rules from undermining the indigenous knowledge that is essential for sustainable development. Himalayan Journal of Sciences 1(2): 74-75, 2003 The full text is available at the SciDevNet website